PENGARUH INDEPENDENSI AUDITOR TERHADAP KUALITAS HASIL AUDIT PADA KANTOR INSPEKTORAT PROVINSI SULAWESI SELATAN - ujianti tawakkal; Nurhaeda Nurhaeda (Fakultas Ekonomi Universitas Indonesia Timur, 2019)
This study aimstoidentify andanalyze theinfluence ofvariableindependence, integrity, objectivityandprofessionalskepticism,auditorseither simultaneouslyorpartially onthe quality of theauditinthe South Sulawesi Provinci alInspectorate. The population in this study were all auditorsin South Sulawesi Province Inspectorate totalling 57 employees. Because the population of ≤100, then all members of the population can be sampled. Thus the sampling method used wassaturated sample orcen susmethod. Data collection methodsused wereobservation, questionnaires, interviews, anddocumentation. Analysis ofthe data usedtotest thehypothesis ofthe study isusing descriptive analysis and statistical analysis using multiple regression. There sultsofhy pothesistesting in this study showth at all independent Variables (independence) have a positiveand significant impact onthe dependent variable (quality audit) in South Sulawesi Province Inspectorate. The magnitude ofthe influence ofa givenindependent variableonthe dependent variableis equal to62.3% while the remaining 37.7% influenced byother factor soutside the model. Skepticismis avariable partially dominant variables affect thequality of theaudit